Influence of Weightbearing Computed Tomography in the Progressive Collapsing Foot Deformity Classification System. (February 2023) - Barbachan Mansur, Nacime Salomão; Lalevée, Matthieu; Lee, Hee Young; Ehret, Amanda; Fayed, Aly; Mann, Tania Szejnfeld; de Carvalho, Kepler Alencar Mendes; de Cesar Netto, Cesar
Background: The objective of this study was to compare progressive collapsing foot deformity (PCFD) classifications performed using clinical and conventional radiographs (CR) with classifications established using clinical and weightbearing computed tomography (WBCT). Methods: This retrospective comparative study evaluated 89 consecutive PCFD feet (84 patients). Three readers performed chart reviews and CR evaluations, determining PCFD classifications that were previously published. After a washout period, the sequence was randomized, and a new classification was executed using clinical and WBCT assessment. One of the readers repeated the WBCT evaluation for intrarater reliability. Results: Interrater reliability for the WBCT was found moderate (0.55) and intrarater excellent (0.98). Evaluation using WBCT produced 29.6% of 1ABC (CR: 25.4%, P = .270), 11.6% of 1ABCD (CR: 6.9%, P = .081), and 6.4% of BC (CR: 3.3%, P = .090) as most prevalent. Class A was presented in 83.9% (CR: 89.5%, P = .55), class B in 89.9% (CR: 76.4%, P < .001), class C in 93.6% (CR: 86.2%, P = .004), class D in 46.4% (CR: 34.8%, P = .006), and class E in 27.7% (CR: 22.5%, P = .158) of the classifications performed by WBCT. Conclusion: WBCT showed a different rate of deformity recognition, which increased the incidence of all classes, especially B, C, and D. An excellent intrarater agreement was found, which infers assessment reliability combining clinical and WBCT evaluation. The obtained information could enhance disease understanding and supply patients with more precise care. Level of Evidence: Level III, retrospective comparative study.